Conjugation of cRGD Peptide to Chlorophyll-a Based Photosensitizer (HPPH) Alters its Pharmacokinetics with Enhanced Tumor-Imaging and Photosensitizing (PDT) Efficacy - Srivatsan, Avinash (2011)
The α(v)β(3) integrin receptor plays an important role in human metastasis and tumor-induced angiogenesis. Cyclic Arg-Gly-Asp (cRGD) peptide represents a selective α(v)β(3) integrin ligand that has been extensively used for research, therapy, and diagnosis of neoangiogenesis. For developing photosensitizers with enhanced PDT efficacy, we here report the synthesis of a series of bifunctional agents in which the 3-(1′-hexyloxyethyl)-3-devinylpyropheophorbide-a (HPPH), a chlorophyll-based photosensitizer was conjugated to cRGD and the related analogs. The cell uptake, in vitro PDT efficacy of the conjugates were studied in α(v)β(3) integrin overexpressing U87 and 4T1 cell lines whereas the in vivo PDT efficacy and fluorescence-imaging potential of the conjugates were compared with the corresponding non-conjugated photosensitizer HPPH in 4T1 tumors. Compared to HPPH, the HPPH-cRGD conjugate in which the arginine and aspartic acid moieties were available for binding to two subunits of α(v)β(3) integrin showed faster clearance, enhanced tumor-imaging and PDT efficacy at 2–4 h post-injection. Molecular modeling studies also confirmed that the presence of HPPH moiety in HPPH-cRGD conjugate does not interfere with specific recognition of cRGD by α(v)β(3) integrin. Compared to U87 and 4T1 cells the HPPH-cRGD showed significantly low photosensitizing efficacy in A431 (α(v)β(3) negative) tumor cells, suggesting possible target-specificity of the conjugate.